FAIRNESS IN SHARIA BUSINESS CONTRACTS: A CONSUMER PROTECTION PERSPECTIVE - Muhammad Farid Rapi; Sinta Kasim; Muhammad Dzaky Abdullah (Universitas Nurul Jadid, 2026)
The development of Islamic business in Indonesia has made significant progress along with the increasing public awareness of the application of Islamic principles in economic transactions. In this context, consumer protection becomes a crucial element, particularly in sharia-based business contracts. This study aims to analyze the concept of consumer protection in sharia business contracts from the perspective of both positive law and Islamic law. The method used is a literature study with a qualitative approach. The results of the study show that positive law, through Law No. 8 of 1999, provides legal-formal protection for consumers, while Islamic law emphasizes moral and spiritual aspects, including the principles of justice, honesty, and the prohibition of gharar and fraud. Although both aim to safeguard consumer rights, they differ in their approaches and the sanctions applied. The integration of positive law and Islamic law can create a more comprehensive consumer protection system in sharia business contracts. This research is expected to contribute ideas to the development of a just and sustainable legal system.